Flow‐pattern evolution of the Laurentide and Cordilleran ice sheets across west‐central Alberta, Canada: implications for ice sheet growth, retreat and dynamics during the last glacial cycle. (27th October 2016) - Atkinson, Nigel; Pawley, Steven; Utting, Daniel J.
ABSTRACT: This paper presents a reconstruction of the geometry, dynamics and flow pattern of the Laurentide and Cordilleran ice sheets along the Albertan portion of the eastern Canadian Rocky Mountains during the last glaciation. Sediment–landform associations relating to the evolution of these ice sheets document their initial convergence and mutual deflection across west‐central Alberta. The continued advance of Laurentide ice locally displaced Cordilleran ice westward into the Front Ranges, and deflected trunk ice emerging from the Athabasca River valley south‐eastwards along the Foothills. These convergent flow patterns remained major features in the regional geometry of both ice sheets throughout the Last Glacial Maximum. The onset of deglaciation was characterized by the northward retreat of the Laurentide Ice Sheet, which progressively unblocked valleys along the mountain front. The configuration of buttress removal initiated the Lateglacial expansion and sequential drawdown of the eastern Cordilleran Ice Sheet along fast‐flowing outlet glaciers. Subsequent regional retreat of Laurentide and Cordilleran ice was associated with the development of large proglacial lakes which amplified deglaciation by destabilizing the margins of both ice sheets, triggering extensive readvances due to periodic changes in water level associated with the opening and closing of outlets by ice margin fluctuations.